Pendidikan Konsep Bhinneka Tunggal Ika dalam Pembelajaran PKn - Herliyanto, Muci (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to examine the role of Civic Education (PKn) in strengthening the national identity of Madrasah Ibtidaiyah (MI) students within a multicultural society. The research employs a library research method with a descriptive qualitative approach. The subject of this study is relevant scholarly literature, while the object focuses on the concept of Civic Education and national identity in the multicultural context of MI. Data collection was carried out through document studies of journal articles, books, and other academic sources from the past five years. Data were analyzed using content analysis techniques by examining themes, concepts, and relevance to the research topic. The findings indicate that Civic Education at MI plays a significant role in shaping students' national identity by teaching values of nationalism, multiculturalism, and character education. The integrative and contextual implementation of PKn encourages students to understand and appreciate cultural, ethnic, and religious diversity within the unity of Indonesia. The study concludes that PKn at MI is a crucial instrument in fostering early nationalism awareness and tolerant attitudes among young generations